2011
DOI: 10.1021/jm1016413
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies To Probe the Phosphoprotein Binding Site on the Carboxy Terminal Domains of the Breast Cancer Susceptibility Gene 1

Abstract: The carboxy terminal BRCT domains of the breast cancer susceptibility gene 1 (BRCA1) bind to a plethora of phosphorylated proteins through a pSXXF consensus recognition motif. BRCT-protein binding regulates key cellular functions such as lipogenesis, cell-cycle checkpoint control and DNA damage response. Identification of the minimal binding sequence and defining the key interactions responsible for biological activity are critical steps in the peptidomimetic design process. Here, we report a systematic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…14,15,60 The highest affinity peptide from this screen had an affinity of 162 nM. Further optimization by Natarajan and coworkers has led to a tetrapeptide with a 40 nM binding affinity 51,61,62 (Fig. 3).…”
Section: Development Of Therapeutic Peptides and Small Molecule Inhibmentioning
confidence: 84%
“…14,15,60 The highest affinity peptide from this screen had an affinity of 162 nM. Further optimization by Natarajan and coworkers has led to a tetrapeptide with a 40 nM binding affinity 51,61,62 (Fig. 3).…”
Section: Development Of Therapeutic Peptides and Small Molecule Inhibmentioning
confidence: 84%
“…The relative binding free energy for ligand X ( X = P2–P14, C1, N1) to ligand P1 is approximated using the half maximal inhibitory concentration IC50 as ΔΔG exp = RT ln IC50( X )/IC50(P1) based on equation Δ G = RT ln K d = RT ln(IC50 + 0.5 C enzyme ) ≈ RT ln IC50 [44, 45]. Binding free energies for L1–L4 are calculated through equation ΔG exp = RT ln ( K d ). a IC50 values of P1–P14 were taken from ref [24]. IC50 values of C1 was taken from ref [27].…”
Section: Methodsmentioning
confidence: 99%
“…These protein–protein interactions play a critical role in the DNA damage response pathway (Cantor et al, 2001; Kim et al, 2007; Liu et al, 2007; Sobhian et al, 2007; Wang et al, 2007). It was shown that tetrapeptides bind BRCT-BRCA1 with nanomolar affinities (Joseph et al, 2010; Yuan et al, 2011a,b). A poly-arginine-tagged tetrapeptide inhibitor blocked the BRCA1–phospho-protein interaction and sensitized cells to PARP inhibition (Pessetto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%